Association Between Indoxyl Sulfate Levels and Major Cardiovascular Events in Hemodialysis Patients with Chronic Kidney Disease - Suhendra, Adi; Ramadani , Sumi; Tarigan , Radar Radius (CoinReads Media Prima, 2025)
Introduction: Chronic kidney disease (CKD) markedly reduces quality of life and increases mortality risk, predominantly due to cardiovascular complications. Indoxyl sulfate, a protein-bound uremic toxin, is increasingly recognized for its role in accelerating cardiovascular disease in CKD patients. This study aims to evaluate the association between indoxyl sulfate levels and major cardiovascular events (MCE) in patients with stage 5 CKD undergoing hemodialysis. Methods: This observational case-control study included 50 patients with stage 5 CKD on hemodialysis. Inclusion criteria were informed consent, willingness to undergo laboratory assessments, and a confirmed CKD diagnosis. Patients with a history of acute myocardial infarction, percutaneous coronary intervention, coronary artery bypass grafting, cardiac arrest, arrhythmias, or incomplete laboratory data were excluded. Serum indoxyl sulfate, creatinine, urea, and estimated glomerular filtration rate (eGFR) were measured. Statistical analyses, including t-tests and logistic regression, were used to compare clinical parameters between patients with and without MCE. Results: Of the 50 patients (mean age: 55.4 ± 8.2 years for MCE group, 47.8 ± 7.9 years for non-MCE group; p=0.015), 29 experienced MCE, and 21 did not. Hemodialysis duration averaged 15.9 ± 4.3 years (MCE) versus 25.9 ± 5.1 years (non-MCE; p=0.005). Significant differences were found in creatinine (p=0.014), creatinine-urea ratio (p=0.007), and eGFR (p<0.001). Elevated indoxyl sulfate levels were strongly associated with MCE (p=0.001). Conclusion: Higher indoxyl sulfate levels are significantly correlated with major cardiovascular events in hemodialysis-dependent CKD patients, underscoring its potential as a predictive biomarker for cardiovascular risk.